(untitled) (Al-Mansour Journal, 2025)
The most difficult task for a robotics researcher is to control the robot manipulator with adequate overall efficiency. This work presents accurate and fast techniques for optimizing the parameters of a 3-DOF robot manipulator, this kind of robot is intended for academic and educational work and it is also used in the medical field. The links of the 3- DOF are all rotary or revolute joints with serial connections. The optimization technique focuses on the Intelligent Swarm algorithms that are used for optimizing and tuning the gain of the proposed controller, which is the conventional Proportional Integral Derivative () is used. The Intelligent Particle Swarm Optimization () and Social Spider Optimization (SSO) have been used for obtaining the best values for the parameters of the controller, to achieve consistency, stability, and robustness. MATLAB/Simulink is used to speed up the computing of FK, IK, and DM of the 3-DOF robot manipulator. The results show that modified PID /SSO gives the best results in terms of stable phase response, minimum Root Means Square Error with the best objective function, stable control signal and reasonable steady-state with perfect trajectory tracking for circular path.